2020
DOI: 10.3390/biology9090300
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Sperm Concentration and Storage Temperature on Goat Spermatozoa during Liquid Storage

Abstract: The use of cooled semen is relatively common in goats. There are a number of advantages of cooled semen doses, including easier handling of artificial insemination (AI) doses, transport, more AI doses per ejaculate, and higher fertility rates in comparison with frozen AI doses. However, cooled semen has a short shelf life. The objective of this study was to examine the effect of temperature and sperm concentration on the in vitro sperm quality during liquid storage for 48 h, including sperm motility and kineti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 58 publications
2
7
0
Order By: Relevance
“…Results of semen preservation at 16 • C in a synthetic extender for 24 h indicate that the semen quality dropped progressively between 0 and 24 h of storage. These observations are in line with previous studies showing that during liquid storage, all variables evaluating motility, viability and normal morphology undergo a significant decrease, regardless of the extender in use, dilution rate, temperature and storage conditions [24,25]. This storage-related quality loss was further subjected to seasonal changes.…”
Section: Discussionsupporting
confidence: 91%
“…Results of semen preservation at 16 • C in a synthetic extender for 24 h indicate that the semen quality dropped progressively between 0 and 24 h of storage. These observations are in line with previous studies showing that during liquid storage, all variables evaluating motility, viability and normal morphology undergo a significant decrease, regardless of the extender in use, dilution rate, temperature and storage conditions [24,25]. This storage-related quality loss was further subjected to seasonal changes.…”
Section: Discussionsupporting
confidence: 91%
“…Progressive sperm motility was slightly modified for the first 48 hr of cooling, and no significant differences between young and adult bucks were detected. Previous studies developed in the same breed (Batista et al., 2011, 2014) showed practically similar values in sperm motility of stored semen at 4°C for 24–48 hr and were comparable when the sperm quality was assessed in chilled semen, whether the diluent used was based on egg yolk (Tabarez et al., 2017) or skimmed milk (Mocé et al., 2020; Sadeghi et al, 2020; Salvador et al., 2006) with medium values between 50% and 65% for the first 48 hr of chilling. In our study, sperm motility was reduced after 72 hr of storage, regardless of the diluent used or the age of the males; as a general rule, as the preservation time increases, a decrease in sperm motility is observed, probably as a consequence of metabolic depletion of sperm (Bashawat et al., 2021), being a fact to take into account, in order to reach an adequate fertility rate.…”
Section: Discussionmentioning
confidence: 65%
“…Gungdogen et al's, 2010 investigation demonstrated these consequences when ram spermatozoa were diluted to 100 × 10 6 sperm/mL and recorded lower membrane damage and oxidative stress compared to spermatozoa diluted to 25 × 10 6 sperm/mL. Research has demonstrated this result in other species with various sperm concentrations, including rabbits [42], cattle [43,44], bucks [45], and pigs [46].…”
Section: Concentration Of Spermatozoamentioning
confidence: 97%